2015
DOI: 10.3892/ol.2015.3828
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of protein phosphatase 5 inhibits ovarian cancer growth in vitro

Abstract: Abstract. Ovarian cancer is the most common cause of gynecological cancer-related mortality. Serine/threonine protein phosphatase 5 (PP5, PPP5C) has been recognized to be involved in the regulation of multiple cellular signaling cascades that control diverse cellular processes, including cell growth, differentiation, proliferation, motility and apoptosis. In this study, to evaluate the functional role of PP5 in ovarian cancer cells, lentivirus-mediated RNA interference (RNAi) was applied to silence PPP5C in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 26 publications
0
5
1
Order By: Relevance
“…The pro-survival effects of PPP6C have been manifested in ultraviolet-B-induced carcinogenesis [ 22 ] and keratinocyte proliferation [ 23 ]. By searching the members of the protein serine/threonine phosphatase family, we found PPP5C could significantly promote the tumor cell proliferation and survival, including HCC [ 34 ], ovarian cancer [ 35 ] and prostate cancer [ 36 ]. Interestingly, knockdown of PPP5C suppressed the proliferation ability, and led to G0/G1 phase arrest, induced cell apoptosis in leukemic cell line U937 cells [ 37 ], which is line with our data showed that PPP6C promoting AML cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…The pro-survival effects of PPP6C have been manifested in ultraviolet-B-induced carcinogenesis [ 22 ] and keratinocyte proliferation [ 23 ]. By searching the members of the protein serine/threonine phosphatase family, we found PPP5C could significantly promote the tumor cell proliferation and survival, including HCC [ 34 ], ovarian cancer [ 35 ] and prostate cancer [ 36 ]. Interestingly, knockdown of PPP5C suppressed the proliferation ability, and led to G0/G1 phase arrest, induced cell apoptosis in leukemic cell line U937 cells [ 37 ], which is line with our data showed that PPP6C promoting AML cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“… 18 Several subsequent studies 19 21 also reported that PPP5C was upregulated in breast cancer, mantle-cell lymphoma and liver cancer tissues, and ascites. Other studies 22 25 reported that downregulation of PPP5C expression could inhibit malignant cells in human glioma, ovarian cancer, hepatocellular carcinoma, and colorectal cancer. The aforementioned findings suggest that PPP5C may play a role in the development and progression of some cancers.…”
Section: Introductionmentioning
confidence: 98%
“…Because inactivating alterations of PP2A subunits have been observed in human cancers and the suppression of the same PP2A components contribute to cell transformation (for review, see ref, 29), many view PP2A as a tumor suppressor. In contrast, PPP5C is found in high levels in several types of human cancers (30)(31)(32)(33)(34)(35), and many lines of evidence indicate that inhibitors of PPP5C may prove useful for the medical management of several types of human cancers (30,32,(36)(37)(38)(39)(40)(41)(42)(43). Therefore, when several carboxamide derivatives containing the 7-oxabicyclo[2.2.1]heptane-2-carboxylic acid moiety shared with LB-100 were identified as novel inhibitors of PPP5C in an ultra-high-throughput screening campaign (44), we were prompted to test LB-100 for inhibitory activity against PPP5C.…”
Section: Introductionmentioning
confidence: 99%